A artikel Penerapan Pendekatan Saintifik Kurikulum 2013 Pada Siswa PAUD TK AL HIDAYAH Kolomayan 01 - Fuadah, Syawiatul (Journal of Childhood Education, Development and Parenting, 2023)
The purpose of this study was to describe the application of the 2013 curriculum scientific approach to PAUD students in Blitar Regency, namely TK Al Hidayah Kolomayan 01. This type of research is descriptive research. One approach to learning in early childhood is a scientific approach. The scientific approach to the 2013 curriculum includes five main activities consisting of the following activities: Observe, question, sample/collect, combine and communicate (decide, present). The 2013 curriculum in PAUD covers all dimensions of child development, namely attitudes, knowledge and skills. And includes all development programs that are integrated and planned and presented according to the child's developmental stage. The application of a scientific approach to children includes principles such as student centering, namely focusing the learning process on children's activities and creativity, not just teacher explanations. The method used in this research is qualitative research using case study method. By identifying, searching literature, determining the appropriate research location, selecting participants, selecting questions, collecting data, analyzing data, interpreting results.